Prevalence and determinants of the metabolic syndrome among subjects with advanced nondiabetes-related chronic kidney disease in Gran Canaria, Spain. (7th February 2016) - Boronat, Mauro; Bosch, Elvira; Lorenzo, Dionisio; Quevedo, Virginia; López-Ríos, Laura; Riaño, Marta; García-Delgado, Yaiza; García-Cantón, César
Abstract: Background The relationship between the metabolic syndrome and mild chronic kidney disease (CKD) has been extensively studied. This study was aimed to estimate the prevalence and factors associated with the metabolic syndrome among subjects with advanced stages of nondiabetes-related CKD.Methods Study population was composed of incident patients with advanced CKD not related to diabetes in a tertiary hospital from Gran Canaria (Spain) since February 2011 to December 2014. Participants fulfilled a survey questionnaire and underwent physical examination and biochemical evaluation.Results The sample was composed of 167 subjects (mean age 63.9 ± 13.7 years; estimated glomerular filtration rate 21.9 ± 6.6 mL/min/1.73 m 2 ). The prevalence of the metabolic syndrome was 68.9% (65.2% in men and 73.3% in women). Highest rates were observed in groups with chronic interstitial nephropathy (80%), CKD of uncertain etiology (76.7%) and CKD related to vascular causes (76.2%). Subjects with metabolic syndrome were older, had higher values of C-reactive protein and more often reported to have first-degree relatives with diabetes and to be physically inactive. In multivariate analyses, age (OR: 1.034 [CI 95%: 1.004–1.065]; p   =  0.024) and family history of diabetes (OR: 2.550 [1.159–5.608]; p  =  0.020) were independently associated with the metabolic syndrome.Conclusions The prevalence of the metabolic syndrome among subjects with advanced nondiabetes-related CKD is high, and greater than that observed in general Canarian population of similar age groups. Age and family history of diabetes are the two factors more strongly associated with the metabolic syndrome in this population.